Model Komunikasi Mauidhoh Hasanah dalam Pendidikan Seksual Remaja Berbasis Keluarga - Awaliyah, Lia; Syamsul, Encu Mulya; Burhani, Ahmad Zacky (Universitas Negeri Padang, 2025)
The background of this study is the low effectiveness of communication between parents and adolescents related to sexual education, which is influenced by parents' limited knowledge and adolescents' discomfort with communicating related to sexual issues in the family. This research aims to offer a communication model of sexual education in the family based on Mauidhoh Hasanah as a solution to the communication barriers found in the field. The research used a qualitative approach with the descriptive-analytical method. Primary data were collected through in-depth interviews with ten parents who have teenagers (aged 17-20 years), observation of communication interactions in the family, as well as an open-ended questionnaire to forty-five teenagers of the same age via WhatsApp. This data was used to understand parents' experiences, family communication patterns, and adolescents' perspectives on sexual education. Secondary data was obtained from a literature review related to the challenges of family sexual education and the principle of Mauidhoh Hasanah, which was analyzed thematically to strengthen the research conceptual framework. Data analysis was carried out with the stages of reduction, presentation, and conclusion drawing according to the Miles and Huberman model. The results showed that sexual education communication in the family is often hampered by parents' limited knowledge and adolescents' discomfort with communicating related to sexual issues in the family. Mauidhoh Hasanah-based communication model that emphasizes gentleness, compassion, wisdom, and exemplary is offered as a conceptual solution to create a more open and effective dialogue atmosphere. However, this model is still conceptual and needs to be further tested so that it can be applied optimally in various family contexts.